Silvinichthys gualcamayo, a new species of catfish from the central Andes of Argentina (Siluriformes: Trichomycteridae) - Fernandez, Luis Alfredo (2013)
Silvinichthys gualcamayo, new species, is described from a stream at 2000 m elevation in the lower slope of the Andean cordillera of San Juan, Argentina. It is distinguished from the three previously described species in the genus by the following combination of characters: the pelvic fin and girdle absent, the caudal peduncle expanded posteriorly toward caudal-fin, the caudal peduncle length 22.0-23.9 % SL, 9-10 dorsal-fin rays, 5-6 branched dorsal-fin rays, 38 vertebrae total, 9 opercular odontodes, 20 interopercular odontodes, 7 pectoral-fin rays, and the wide supraorbital tendon bone.